Do not repeat old mistakes in learning from accidents: It`s better to prevent a run away than be ready for it - Ferjenčík, Miloš; Čížek, Oldřich (Agifter, 2018)
The article returns to more than twenty years old, but very serious, accident from the Czech railways. It briefly reminds WHAT happened that time, and analyzes HOW and WHY the causal factors leading to the accident were combined. Lessons learned from the analysis are compared with available data. It turns out that surprisingly, in the course of the lessons learning, the possibilities for the prevention of initiating the basic hazard, which realized in the accident, have not been thoroughly analyzed. Therefore, it cannot be said that the accident was properly used as information to prevent similar accidents. Two recent media reports confirm that the basic hazard keeps being urgent and that the appropriate lessons are still missing. Therefore, the answer to the question from the seminar “what are the remaining challenges?” is: In the accident analysis, it is especially necessary to consistently accept and implement already known approaches to the analysis of causes and to the accident response, including the application of known principles for inherently safer solutions. Consistent work with existing tools is often everything what is necessary for satisfactory lessons learning. In the case described, it should not be forgotten that "When a scenario cannot be initiated, it is not necessary to mitigate it."
Neopakujme při poučování z nehod staré chyby: Lepší je předejít ujetí, než být na ně připraven
Keywords: Railway safety; Root cause analysis; Inherently safer design; Bezpečnost železnice, analýza kořenových příčin, inherentně bezpečnější projektování